Engineering Legitimacy How Institutional Entrepreneurs in E-Commerce Bring Fashion Companies into the Digital Age - Petkova, Iva (Springer International Publishing, 2018)
Through the lens of the fashion industry, Iva Petkova explores not only how institutionalized organizations react and adapt to the rise of start-up outsiders, but also how these outside "disruptors" seek to cultivate legitimacy and win influence. In so doing, she reflects upon a longstanding question in the sociology of organizations and neo-institutional theory: How do institutionalized organizations in creative industries resolve the inherent conflict between art and commerce, particularly in a changing institutional environment? Engineering Legitimacy outlines the processes through which e-commerce and social commerce companies in fashion disturb and reconstruct the industry, crosscutting their technical field of expertise and looking to legitimize their innovative practice in the institutionally elaborated field of fashion. Through an analysis of the emerging culture of innovation collectively created by start-up outsider disruptors, this book contemplates how fashion-technology companies transform their moral narratives into acceptable commercial practice, legitimating a model of profound institutional change over the digital operations of fashion companies.